Hospitalization time is associated with weight gain in forensic mental health patients - A.L. Pedersen; F. Gildberg; P. Hjorth; M. Højlund; K. Andersen (European Psychiatry, 2022)
Introduction Previous studies have found substantial weight gains in forensic mental health patients (FMHP) during hospitalisation. However, previous studies have not compared in- and outpatients, thus the weight change could be a general change over time. Research on the association between proportional hospitalization time (PHT) and weight change is lacking.